The future of retention forestry : the historical legacy in stands and its impact on retention in the next generation - Lindblad, Jan (SLU/Dept. of Forest Ecology and Management, 2019)
Today, around 55% of the world’s forests are already managed for timber pro-duction and other values. The need for actions concerning the fast decline in biodiversity was in the late 20th century met by the uprising of retention forest-ry. Retention forestry integrates conservation in commercially managed stands, enabling variation, connectivity, and continuity across the landscape, which makes it an important supplementary strategy to protected areas. However, there are uncertainties around retention practices effectiveness to protect all functional groups of species because some of them depend on certain ecologi-cal structures (e.g. old trees, deciduous tree, and dead wood). Here, I use the term Ecologically Valuable Retention Trees (EVRTs) to describe trees that either have potential to develop or already have high ecological value. The Swedish Cellulose Company (SCA) is a major forestry actor in Sweden. Most stands that SCA final-fell today originate from forests shaped by selective cut-ting, while in the future most stands will originate from already cultivated for-ests. The overall aim of my study is to forecast what SCA’s possibili-ties/restrains for retaining EVRTs and deciduous trees throughout final-felling will be in the future. By comparing stands that have been cultivated/clear-cut (CC) with stands that have never been clear-cut (NC), I focus on potential dif-ferences between the two stand types. I also discuss how this difference should influence the retention strategy within SCA and Swedish forestry. My study was performed in the county of Västerbotten in northern Sweden. I measured the number of EVRTs and the proportion of deciduous tree species in 14 NC and 14 CC spruce dominated stands (systematically sampled with a PPS meth-od). 10 sample plots with a 10-meter radius were systematically fitted within each stand. My results show that there will be less EVRTs in the future and that the deciduous proportions will remain similar. There are potential ways to mit-igate the lack of ecologically ...